The social contract with endogenous sentiments - Matteo Cervellati; Joan Esteban; Laurence Kranich (Institute for the Study of Labor (IZA), 2006)
In this paper we present a model of rational voting over redistribution where individual self-esteem and relative esteem for others are endogenously determined. Individuals differ in their productivities, and their behaviour and political views are influenced by moral standards concerning work. Agents determine what they take to be proper behaviour and they judge others, and themselves, accordingly, increasing their esteem (or self-esteem) for those who perform in excess of the standard and decreasing their esteem for those who work less. The desired extent of redistribution depends both on individual income and on individual attitudes toward others. The model has two types of equilibria. In a cohesive equilibrium, all individuals conform to the standard of proper behaviour, income inequality is low and social esteem is not biased toward any particular type. Under these conditions equilibrium redistribution increases in response to larger inequality. In a clustered equilibrium skilled workers work above the mean while unskilled workers work below. In such an equilibrium, income inequality is large and sentiments are biased in favor of the industrious. As inequality increases, this bias may eventually overtake the egoistic demand for greater taxation and equilibrium redistribution decreases. The type of equilibrium to emerge crucially depends on inequality. We contrast the predictions of the model with data on inequality, redistribution, work values and attitudes toward work and toward the poor for a set of OECD countries
Keywords: 330